Elastins from patients with Williams–Beuren syndrome and healthy individuals differ on the molecular level. Issue 7 (17th June 2016) - Heinz, Andrea; Huertas, Angela C. Mora; Schräder, Christoph U.; Pankau, Rainer; Gosch, Angela; Schmelzer, Christian E. H.
Abstract : Williams–Beuren syndrome (WBS) is a congenital disorder, which involves the heterozygous deletion of the elastin gene and other genes on chromosome 7. Clinical symptoms that are associated with hemizygosity of the essential extracellular matrix protein elastin include premature aging of the skin and supravalvular aortic stenosis. However, only little is known about the molecular basis of structural abnormalities in the connective tissue of WBS patients. Therefore, for the first time this study aimed to systematically characterize and compare the structure and amount of elastin present in skin and aortic tissue from WBS patients and healthy individuals. Elastin fibers were isolated from tissue biopsies, and it was found that skin of WBS patients contains significantly less elastin compared to skin of healthy individuals. Scanning electron microscopy and mass spectrometric measurements combined with bioinformatics data analysis were used to investigate the molecular‐level structure of elastin. Scanning electron microscopy revealed clear differences between WBS and healthy elastin. With respect to the molecular‐level structure, it was found that the proline hydroxylation degree differed between WBS and healthy elastin, while the tropoelastin isoform appeared to be the same. In terms of cross‐linking, no differences in the content of the tetrafunctional cross‐links desmosine and isodesmosine were found between WBS and healthy elastin. However, principal component analysis revealed differences between enzymatic digests of elastin from healthy probands and WBS patients, which indicates differing susceptibility toward enzymatic cleavage. Overall, the study contributes to a better understanding of the correlation between genotypic and elastin‐related phenotypic features of WBS patients. © 2016 Wiley Periodicals, Inc.